Novel functions of the Arabidopsis transcription factor TCP5 in petal development and ethylene biosynthesis. (25th April 2018) - van Es, Sam W.; Silveira, Sylvia R.; Rocha, Diego I.; Bimbo, Andrea; Martinelli, Adriana P.; Dornelas, Marcelo C.; Angenent, Gerco C.; Immink, Richard G.H.
Summary: The flowers of most dicotyledons have petals that, together with the sepals, initially protect the reproductive organs. Later during development petals are required to open the flower and to attract pollinators. This diverse set of functions demands tight temporal and spatial regulation of petal development. We studied the functioning of the Arabidopsis thaliana TCP5 ‐like transcription factors (TFs) in petals. Overexpression of TCP5 in petal epidermal cells results in smaller petals, whereas tcp5 tcp13 tcp17 triple knockout lines have wider petals with an increased surface area. Comprehensive expression studies revealed effects of TCP5 ‐like TFs on the expression of genes related to the cell cycle, growth regulation and organ growth. Additionally, the ethylene biosynthesis genes 1‐amino‐cyclopropane‐1‐carboxylate (ACC) synthase 2 ( ACS2 ) and ACC oxidase 2 ( ACO2 ) and several ETHYLENE RESPONSE FACTORS ( ERF s) are found to be differentially expressed in TCP5 mutant and overexpression lines. Chromatin immunoprecipitation–quantitative PCR showed direct binding of TCP5 to the ACS2 locus in vivo . Ethylene is known to influence cell elongation, and the petal phenotype of the tcp5 tcp13 tcp17 mutant could be complemented by treatment of the plants with an ethylene pathway inhibitor. Taken together, this reveals a novel role for TCP5‐like TFs in the regulation of ethylene‐mediated petal development and growth. Significance Statement: Comprehensive expression studies revealed effects of the Arabidopsis TCP5 ‐like transcription factors on the expression of cell cycle‐, growth regulation‐, and organ growth‐related genes. TCP5 is shown to directly inhibit ethylene biosynthesis by binding the ACS2 locus, which might explain the observed phenotypes in cell elongation during petal development. This adds TCP5 to the growing list of TCP genes involved in hormone biosynthesis and signalling.